2020
DOI: 10.46405/ejms.v2i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Of primary Total Hip Arthroplasty using Harris Hip Score in Arthritic Hip

Abstract: Introduction: Total hip arthroplasty (THA) is a well-established procedure for advanced arthritis of the hip joint. It significantly improves the quality of life by relieving pain and improving functional disability. The objective of this study was to evaluate the clinical and functional outcome of primary total hip arthroplasty using the Harris Hip Score. Method: Prospective study was conducted in Civil Service Hospital. Out of 145 THA performed from Jan 2014 to Dec 2018, the first 100 cases that fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The demographic characteristics of the study population are consistent with those reported in other studies evaluating THR outcomes. The mean age of 65.3 years and the distribution of sexes (52.5% male and 47.5% females) are similar to those reported by Marahatta et al and Khan et al 15,16 The mean BMI of 28.4 (SD±3.8) kg/m 2 aligns with the findings of Wang et al 17 consistent with the findings of other studies. Fortin et al 18 also reported significant improvements in PCS scores and a slight decline in MCS scores after THR.…”
Section: Discussionsupporting
confidence: 90%
“…The demographic characteristics of the study population are consistent with those reported in other studies evaluating THR outcomes. The mean age of 65.3 years and the distribution of sexes (52.5% male and 47.5% females) are similar to those reported by Marahatta et al and Khan et al 15,16 The mean BMI of 28.4 (SD±3.8) kg/m 2 aligns with the findings of Wang et al 17 consistent with the findings of other studies. Fortin et al 18 also reported significant improvements in PCS scores and a slight decline in MCS scores after THR.…”
Section: Discussionsupporting
confidence: 90%
“…Avascular necrosis of hip (44%) was the major indication for total hip replacement, followed by primary osteoarthritis (25%) and post-traumatic osteoarthritis (25%). A study conducted by Marahatta SB et al also shows that avascular necrosis of hip (36%) and primary osteoarthritis (24%) are the is the major indications for total hip replacement [3].…”
Section: Discussionmentioning
confidence: 92%
“…These results are comparable to study conducted Marahatta SB et al according to this study 2 % of patient were having superficial skin infection postoperatively and 2% of patients were having postoperative hip dislocations. All these patients were conservatively managed [3]. other complications found on literature search in similar studies are aseptic loosening, osteolysis, and symptomatic failure of both acetabular and femoral components.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations